Development of a Differentiated Learning Model to Improve Student Academic Achievement in Economics Learning at SMAN 5 Cirebon - Kharisma, Dina Citra; Herawan, Endang; Senja Wiraning Fury, Nurul (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to determine the improvement of student academic achievement after the implementation of a differentiated learning model in economics learning at SMAN 5 Cirebon, and to identify teacher strategies in integrating content, process, and product differentiation in economics learning.Method: This research employed a qualitative descriptive approach with the economics teacher and students of class X-7 as subjects, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model with data validity ensured through source, technique, and time triangulation. Results: The findings reveal that the implementation of the differentiated learning model had a significantly positive impact on student academic achievement, marked by an increased number of students meeting the Minimum Competency Criterion (KKM), more evenly distributed scores, and enhanced student engagement and conceptual understanding of economics. Teacher strategies encompassed content differentiation through varied VAK-based learning resources (visual, auditory, kinesthetic); process differentiation through prompting questions, small groups with assigned roles, and random questioning techniques; and product differentiation through task options aligned with learning styles — posters for visual learners, oral presentations for auditory learners, and videos or simulations for kinesthetic learners — while maintaining the same learning objectives. Novelty: The VAK modality-based identification of student learning styles served as the primary foundation for all differentiation strategies, although implementation is still in the development stage and faces challenges such as time constraints and classroom management complexity.